The curricular stage supervised in physical education: teaching knowledge and the theory-practical relationship - Carvalho Filho, Josue Jose de; Azevedo Brasileiro, Tania Suely; Neto, Samuel de Souza [UNESP] (Univ Fed Sao Carlos, 2019)
This work discuss the supervised internship in the formation of the Physical Education teacher from the knowledge and the theory-practice relationship. The research was descriptive/qualitative carried out in a university of the Amazon. Participated in the study 14 students and 2 teachers. The instruments were questionnaire and interview. The data processing was done through interactive triangulation and content analysis. The results indicated that the organization of the internship provided in the Pedagogical Project of Course (PPC) complies with the. However, in the teachers' voices some gaps were evident, among which the following stand out: the need to regulate the internship and lack of inte Although students and teachers perceive that there is a link between theory and practice to mobilize knowledge in the internship, it has been shown that this consolidation depends on the connection between the university, school, documents, teacher educators, managers and students in formation.gration among teachers.
Keywords: Supervised stage; Physical education in the Amazon; Teacher knowledge; Theory-practice relationship